A NiCuZn material used in power inductor components and a preparation method thereof

Through the specific ratio of NiCuZn materials and additives, the magnetic permeability and mechanical properties are optimized, and the deformation and performance improvement of NiCuZn ferrite materials in power inductor components is solved, achieving higher inductor component performance and reliability.

CN118969430BActive Publication Date: 2025-01-14ZHONGSHAN DONGCHEN MAGNETIC ELECTRONICS PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410998789.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-01-14
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The deformation problems and performance improvement of NiCuZn ferrite materials in power inductor components are difficult to effectively control, affecting the inductance value and superposition performance.

Method used

Using a specific ratio of NiCuZn material, including the first principal component (Fe2O3, ZnO, NiO, CuO) and the second principal component (scrapped NiCuZn material), and optimizing the magnetism through additives (V2O5, SiO2, CaO, Bi2O3, SrO) Conductivity and mechanical properties, reduce sintering stress, and improve material density and uniformity.

Benefits of technology

Effectively optimize the magnetic permeability and saturated magnetic induction strength of NiCuZn material, reduce magnetic loss, improve the superposition performance and overall reliability of inductor components, reduce resource waste, and improve sintering behavior through recycling and pretreatment, reducing inductor Risk of deformation of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118969430B_ABST
    Figure CN118969430B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of ferrites, and discloses a NiCuZn material used in power inductor components and a preparation method thereof. A NiCuZn material used in power inductor components comprises a first main component, a second main component and an additive; the first main component comprises the following raw materials: Fe 2 O 3 , ZnO, NiO, and the balance is CuO; based on the weight of the first main component, the additives include the following weight percentage raw materials: 0.01-0.3wt% V 2 O 5 , 0.01‑0.2wt%SiO 2 and 0.01-0.2wt%CaO; the second main component is scrapped NiCuZn material. The application adopts specific raw materials, specific ratios and specific processing technology to effectively optimize the magnetic permeability and saturation magnetic induction intensity of NiCuZn materials, providing good basic performance for power inductor components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ferrites, and in particular to a NiCuZn material used in power inductor components and a preparation method thereof. Background Art

[0002] NiCuZn ferrite material is a soft magnetic composite material formed by mixing iron, nickel, copper and zinc oxides in a specific proportion and sintering at high temperature. Due to its advantages such as high magnetic permeability, high saturation magnetic induction intensity, good temperature stability and low loss, it is widely used in the manufacture of various power inductor components, such as RI (Rectangular Inductors) components, which are often used in power management and electromagnetic compatibility (EMC) solutions in the fields of switching power supplies, inverters, communication equipment, automotive electronics, new energy systems, etc.

[0003] Power inductor components made of NiCuZn ferrite materials have become one of the preferred soft magnetic components in many electronic devices due to their excellent magnetic properties and thermal stability.

[0004] However, during the production process, NiCuZn ferrite materials are easily affected by the characteristics of raw materials and production process conditions. These factors not only affect the performance of the NiCuZn ferrite material itself, but also cause deformation problems in the final RI power inductor components, thereby affecting its inductance value and superposition performance.

[0005] Therefore, there is an urgent need to provide a NiCuZn ferrite material to achieve deformation control and performance improvement of the NiCuZn ferrite material in power inductor component applications. Summary of the invention

[0006] In order to solve at least one of the above technical problems, a NiCuZn ferrite material is developed to achieve deformation control and performance improvement of the NiCuZn ferrite material in power inductor component applications. The present application provides a NiCuZn material for use in power inductor components and a preparation method thereof.

[0007] In a first aspect, the present application provides a NiCuZn material for use in a power inductor component, comprising a first main component, a second main component and an additive; wherein the first main component comprises the following raw materials in weight percentage: 64-67wt% Fe 2 O 3 , 13-16wt% ZnO, 10-14wt% NiO, the balance is CuO;

[0008] Based on the weight of the first main component, the additive includes the following weight percentage raw materials: 0.01-0.3wt% V 2 O5 , 0.01-0.2wt%SiO 2 and 0.01-0.2wt% CaO;

[0009] The second main component is scrapped NiCuZn material; the added amount of the second main component is 10-30wt% of the weight of the first main component.

[0010] By adopting the above technical scheme, the raw materials of the present application adopt a specific first main component, a second main component and additives as well as a specific ratio, which can effectively optimize the magnetic permeability, saturation magnetic induction intensity and low magnetic loss of the NiCuZn material, provide good basic performance for power inductor components, and at the same time have excellent DC current superposition performance.

[0011] The second main component of the present application uses scrapped NiCuZn materials as recycled resources, which reduces resource waste. By introducing recycled materials with certain microstructures and grain sizes, it helps to improve the sintering behavior of new synthetic materials and reduce the internal stress generated during the sintering process, thereby reducing the deformation risk of the inductor component.

[0012] Further, the additive comprises the following weight percentage raw materials: 0.08-0.22wt% V 2 O 5 , 0.06-0.15wt%SiO 2 and 0.07-0.12wt%CaO.

[0013] Furthermore, the additive also includes 0.1-0.26wt% Bi 2 O 3 and / or 0.05-0.3wt% SrO.

[0014] By adopting the above technical solution, the specific additives used in this application are helpful to inhibit grain growth, reduce internal stress, and improve the mechanical properties and magnetic properties of the material. The CaO and SrO added in this application can adjust the sintering activity and phase composition and promote densification; Bi 2 O 3 It helps to form a low-melting-point glass phase, promotes sintering densification and reduces sintering temperature, and effectively improves particle diffusion in the raw materials, increases particle contact surface, and thereby improves the material microstructure, reduces sintering stress, and improves the mechanical strength and magnetic properties of the material.

[0015] In a second aspect, the present application provides a method for preparing the NiCuZn material used in the power inductor component, comprising the following steps:

[0016] S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material;

[0017] S2, mixing the additive with the pre-sintered material obtained in step S1, and performing secondary ball milling to obtain a mixed material;

[0018] S3, mixing the second main component with the mixed material obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing and molding, and sintering to obtain the NiCuZn material used in the power inductor element.

[0019] Furthermore, in the step S1, the pre-burning temperature is 800-900°C and the holding time is 2-5h.

[0020] Furthermore, in the step S2, the particle size of the mixture after the secondary ball milling is 0.8-1 μm.

[0021] Furthermore, in step S3, the adhesive is selected from a polyvinyl alcohol solution, and the weight of the polyvinyl alcohol is 0.6-2.2 wt % of the weight of the mixture.

[0022] Furthermore, in step S3, the second main component is mixed and stirred with the mixed material after being pretreated, and the pretreatment includes the following steps:

[0023] The second main component is ball-milled to control the particle size to 1.5-3 μm, placed in a 10-15wt% nitric acid solution, heated to 80-100°C, and kept warm for 20-30 minutes; filtered, washed, dried, plasma treated, and a copper grain layer is plated on the surface of the second main component by vacuum evaporation to obtain a pretreated second main component.

[0024] Furthermore, during the plasma treatment process, the treatment atmosphere includes a mixed gas of nitrogen and oxygen in a volume ratio of 1-3:5; the gas flow rate of the atmosphere is 260-300sccm; the treatment voltage is 300-370V; and the power is 3-4kW.

[0025] Furthermore, during the vacuum evaporation copper plating process, the thickness of the copper grain layer is 50-100 nm.

[0026] Furthermore, the deposition amount of the copper grain layer is 0.1-0.4wt% of the total mass of the second main component.

[0027] Furthermore, in step S3, during the sintering process, the temperature is increased to 240-280°C at a heating rate of 3-5°C / min in the first stage, and the temperature is increased to 1050-1100°C at a heating rate of 1.2-2°C / min in the second stage, and then kept warm for 2.5-4h. The temperature is cooled at a cooling rate of 1.5-2°C / min in the third stage, and the temperature is kept warm for 5min every time the temperature is reduced by 80-150°C, until the obtained NiCuZn material is cooled to room temperature.

[0028] By adopting the above technical scheme, in the process of preparing NiCuZn material, the present application controls the size of the original mixed material and the waste material so that the material before pressing reaches the densest packing state, and obtains a high-density blank, thereby effectively improving the sintering quality of the material; by pre-treating the waste NiCuZn material, immersing it in nitric acid and then performing plasma treatment, the active particles in the plasma interact with the surface of the waste NiCuZn powder, thereby enhancing the surface energy and reaction characteristics of the waste NiCuZn powder, activating it, thereby promoting the waste The powder is better compatible with the mixture during sintering, thereby improving the uniformity of the prepared NiCuZn; by vacuum evaporation copper plating on the waste NiCuZn powder after plasma treatment, the copper grain layer reacts with oxygen at the initial stage of sintering to generate copper oxide, which can be used as a sintering aid to promote the sintering of the powder at a lower temperature, help to achieve low-temperature sintering and increase the density of the material; in addition, the deposition of copper grains may enhance the mechanical strength of the prepared NiCuZn ferrite material, improve its wear resistance and pressure resistance during processing, and reduce porosity and defects during sintering.

[0029] In summary, the present invention includes at least one of the following beneficial technical effects:

[0030] 1. The raw materials of the present application use a specific first main component, a second main component and an additive as well as a specific ratio, which can effectively optimize the magnetic permeability and saturation magnetic induction intensity of the NiCuZn material;

[0031] 2. The second main component of the present application uses scrapped NiCuZn materials as recycled resources, which reduces resource waste and brings better microscopic properties and sintering properties by pre-treating them, which helps to improve the sintering behavior of the new synthetic material and reduce the internal stress generated during the sintering process, thereby reducing the deformation risk of the inductor component;

[0032] 3. The specific additives used in this application help to inhibit grain growth, reduce internal stress, and improve the mechanical and magnetic properties of the material; thereby improving the stacking performance and overall reliability of the power inductor component. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the differential thermal curve of the NiCuZn material prepared in Example 2;

[0034] Figure 2 This is the differential thermal curve of the NiCuZn material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0036] The present application designs a NiCuZn material used in power inductor components, including a first main component, a second main component and an additive; wherein the first main component includes the following raw materials in weight percentage: 64-67wt% Fe 2 O 3 , 13-16wt% ZnO, 10-14wt% NiO, the balance is CuO;

[0037] Based on the weight of the first main component, the additive includes the following weight percentage raw materials: 0.01-0.3wt% V 2 O 5 , 0.01-0.2wt%SiO 2 and 0.01-0.2wt% CaO;

[0038] The second main component is scrapped NiCuZn material; the added amount of the second main component is 10-30wt% of the weight of the first main component.

[0039] The NiCuZn material used in the power inductor element provided in the present application is prepared by the following method, including the following steps:

[0040] S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material;

[0041] S2, mixing the additive with the pre-sintered material obtained in step S1, and performing secondary ball milling to obtain a mixed material;

[0042] S3, mixing the second main component with the mixed material obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing and molding, and sintering to obtain the NiCuZn material used in the power inductor element. Specific embodiments

[0044] The raw material models of this application are as follows. Unless otherwise specified, the raw materials of this application are all commercially available:

[0045] Fe 2 O 3 : purity 99%; ZnO: purity 99%; NiO: purity 98.5-99%; CuO: purity 99.9%; SiO 2 : Purity 99.9%; V 2 O 5 : purity 99.99%; CaO: purity 99%; Bi 2 O 3 : purity 99%; SrO: purity 99%.

[0046] Test items and methods:

[0047] Magnetic permeability (μi): tested on E4991A low frequency impedance analyzer + 16454A test fixture, magnetic permeability μi test at 13.56MHz frequency;

[0048] Insulation resistivity (ρ): Use Agilent4339B high resistance meter to test the insulation resistance value R at both ends of NiCuZn material and calculate the insulation resistivity ρ;

[0049] Inductance change rate (ΔL): When a 3A DC bias current is applied, the inductance of the inductor component changes relative to the initial inductance (denoted as L) when there is no DC bias (i.e., only AC or pulse current) 0 ) change; wherein, after winding 20 turns on the prepared NiCuZn material, the inductance value was measured using LCR.

[0050] Examples 1-3

[0051] The raw material formula of NiCuZn material used in power inductor components of Examples 1-3 is shown in Table 1.

[0052] Table 1

[0053]

[0054]

[0055] The second main component is scrapped NiCuZn material, and the scrapped NiCuZn material is recycled NiCuZn material, wherein the main component includes the following weight percentage raw materials: 67wt% Fe 2 O 3 , 13wt% ZnO, 12wt% NiO, and the balance is CuO.

[0056] The method for preparing the NiCuZn material used in the power inductor element in Example 1 comprises the following steps:

[0057] S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material;

[0058] S2, mixing the additive with the pre-sintered material obtained in step S1, and performing secondary ball milling to obtain a mixed material;

[0059] S3, mixing the second main component with the mixture obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing into a green body with a specification of φ25×φ15×7.5mm, sintering, and obtaining a NiCuZn material.

[0060] In S1, the pre-burning temperature is 800°C and the holding time is 5h;

[0061] In S2, the average particle size of the mixture was 0.8 μm;

[0062] In S3, the binder is a polyvinyl alcohol solution with a concentration of 12 wt%, and the weight of the polyvinyl alcohol is 2.2 wt% of the weight of the mixture;

[0063] In S3, the pretreatment process of the second main component only includes ball milling it to control the average particle size of the second main component to be 3μm; in S3, during the sintering process, the temperature is raised to 250℃ at a heating rate of 3-5℃ / min in the first stage, and the temperature is raised to 1050℃ at a heating rate of 1.4℃ / min in the second stage, and then kept warm for 3h, and the third stage is cooled at a cooling rate of 1.5℃ / min, and the temperature is kept warm for 5min every time the temperature is reduced by 120℃, until the obtained NiCuZn material is cooled to room temperature.

[0064] The method for preparing the NiCuZn material used in the power inductor element in Example 2 comprises the following steps:

[0065] S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material;

[0066] S2, mixing the additive with the pre-sintered material obtained in step S1, and performing secondary ball milling to obtain a mixed material;

[0067] S3, mixing the second main component with the mixture obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing into a green body with a specification of φ25×φ15×7.5mm, sintering, and obtaining a NiCuZn material.

[0068] In S1, the pre-burning temperature is 850°C and the holding time is 3h;

[0069] In S2, the average particle size of the mixture was 0.9 μm;

[0070] In S3, the binder is a polyvinyl alcohol solution with a concentration of 12 wt%, and the weight of the polyvinyl alcohol is 1.5 wt% of the weight of the mixture;

[0071] In S3, the pretreatment process of the second main component only includes ball milling the second main component to control the average particle size of the second main component to be 2.4 μm;

[0072] In S3, during the sintering process, the temperature was raised to 250°C at a heating rate of 3-5°C / min in the first stage, and was raised to 1050°C at a heating rate of 1.4°C / min in the second stage, and then kept warm for 3 hours. In the third stage, the temperature was cooled at a cooling rate of 1.5°C / min, and the temperature was kept warm for 5 minutes every time the temperature was reduced by 120°C, until the obtained NiCuZn material was cooled to room temperature.

[0073] The method for preparing the NiCuZn material used in the power inductor element in Example 3 comprises the following steps:

[0074] S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material;

[0075] S2, mixing the additive with the pre-sintered material obtained in step S1, and performing secondary ball milling to obtain a mixed material;

[0076] S3, mixing the second main component with the mixture obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing into a green body with a specification of φ25×φ15×7.5mm, sintering, and obtaining a NiCuZn material.

[0077] In S1, the pre-burning temperature is 900°C and the holding time is 2h;

[0078] In S2, the average particle size of the mixture is 1 μm;

[0079] In S3, the binder is a polyvinyl alcohol solution with a concentration of 12 wt%, and the weight of the polyvinyl alcohol is 0.6 wt% of the weight of the mixture;

[0080] In S3, the pretreatment process of the second main component only includes ball milling the second main component to control the average particle size of the second main component to be 1.5 μm;

[0081] In S3, during the sintering process, the temperature was raised to 250°C at a heating rate of 3-5°C / min in the first stage, and was raised to 1050°C at a heating rate of 1.4°C / min in the second stage, and then kept warm for 3 hours. In the third stage, the temperature was cooled at a cooling rate of 1.5°C / min, and the temperature was kept warm for 5 minutes every time the temperature was reduced by 120°C, until the obtained NiCuZn material was cooled to room temperature.

[0082] Embodiment 4-7

[0083] Examples 4-7 are based on Example 2, except that the weights of the additives are different.

[0084] The additives in Example 4 include the following raw materials in weight percentage: 0.08 wt % V 2 O 5 、0.15wt%SiO 2 and 0.12wt%CaO.

[0085] The additives in Example 5 include the following raw materials in weight percentage: 0.15 wt % V 2 O 5 、0.1wt%SiO 2 and 0.1wt%CaO.

[0086] The additive in Example 6 includes the following raw materials in weight percentage: 0.22 wt % V 2 O 5 、0.06wt%SiO 2 and 0.07wt%CaO.

[0087] The additives in Example 7 include the following raw materials in weight percentage: 0.3 wt % V 2 O 5 , 0.01wt%SiO 2 and 0.01wt%CaO.

[0088] Embodiment 8-9

[0089] Examples 8-9 are based on Example 5, with the difference that the average particle size of the second main component is different.

[0090] The average particle size of the second main component in Example 8 was 1.5 μm.

[0091] The average particle size of the second main component in Example 9 was 3 μm.

[0092] Examples 10-14

[0093] Example 10 is based on Example 5, except that: 0.1 wt% Bi is added as an additive. 2 O 3 .

[0094] Example 11 is based on Example 5, except that 0.05 wt % SrO is further added as an additive.

[0095] Example 12 is based on Example 5, except that: 0.1 wt% Bi is added as an additive. 2 O 3 and 0.05wt%SrO.

[0096] Example 13 is based on Example 5, except that: 0.16 wt% Bi is added as an additive. 2 O 3 and 0.18wt%SrO.

[0097] Example 14 is based on Example 5, except that: 0.26 wt% Bi is added as an additive. 2 O 3 and 0.3wt%SrO.

[0098] Embodiment 15

[0099] Embodiment 15 is based on Embodiment 13, except that: in the preparation process of the NiCuZn material in Embodiment 15, in step S3, before the second main component is mixed and stirred with the mixed material, the pretreatment process includes the following steps:

[0100] The second main component is ball-milled to control the average particle size to 2.4 μm, placed in a 10wt% nitric acid solution, heated to 80°C, and kept warm for 30 minutes; filtered, washed, and dried, and then plasma treated in a mixed gas atmosphere of nitrogen and oxygen with a volume ratio of 2:5, with the gas flow rate set to 300sccm, the voltage set to 350V, and the power set to 3kW; then a copper grain layer is plated on the surface of the second main component after plasma treatment by vacuum evaporation, and the average thickness of the copper grain layer on the surface of the scrapped NiCuZn powder is controlled to be 100nm, so as to obtain the pretreated second main component.

[0101] Comparative Example 1

[0102] Comparative Example 1 is based on Example 2, except that: the second main component is not added during the preparation of the NiCuZn material in Comparative Example 1.

[0103] Comparative Example 2

[0104] Comparative Example 2 is based on Example 2, except that: the raw material of the first main component in Comparative Example 2 is: 62wt% Fe 2 O 3 , 10wt% ZnO, 18wt% NiO, 10wt% CuO.

[0105] Comparative Example 3

[0106] Comparative Example 3 is based on Example 2, except that the additive in Comparative Example 3 includes 0.2 wt % SiO 2 and 0.2wt%CaO.

[0107] Comparative Example 4

[0108] Comparative Example 4 is based on Example 2, except that the additive in Comparative Example 4 includes 0.01 wt% V 2 O 5 and 0.2wt%CaO.

[0109] Comparative Example 5

[0110] Comparative Example 5 is based on Example 2, except that the additive in Comparative Example 5 includes 0.2 wt % SiO 2 and 0.01wt%V 2 O 5 .

[0111] Comparative Example 6

[0112] Comparative Example 6 is based on Example 2, except that the additive in Comparative Example 6 includes 0.4 wt % V 2 O 5 , 0.3wt%SiO 2 and 0.3wt%CaO.

[0113] Performance Testing

[0114] 1. The NiCuZn materials prepared in Examples 1-15 and Comparative Examples 1-6 were tested for saturation magnetic induction, magnetic permeability, insulation resistivity and inductance change rate (3A), respectively. The test results are shown in Table 2.

[0115] 2. The differential thermal curves of the NiCuZn materials prepared in Example 2 and Comparative Example 1 were measured respectively. The test results are shown in Figure 1 and Figure 2 .

[0116] Table 2

[0117]

[0118]

[0119] It can be seen from Examples 1-3, Comparative Examples 1-6 and Table 2 that the NiCuZn material prepared by the present application using specific raw materials and specific contents has excellent comprehensive performance, a saturation magnetic flux density of 370.1-426.2 mT, a magnetic permeability of 320.6-420.1, and a low inductance change rate of less than 8.5%; It can be seen from Examples 4-7 that the additives of the present application use a more optimal ratio, and the comprehensive performance of the NiCuZn material prepared is more excellent; It can be seen from Examples 8-9 that the present application can effectively improve the mixing uniformity of the material and reduce the sintering stress and improve the comprehensive performance of the NiCuZn material by controlling the average particle size of the second main component; It can be seen from Examples 10-14 that the present application also adds CaO and SrO to adjust the sintering activity and phase composition and promote densification; Bi 2 O 3 It helps to form a low-melting-point glass phase, promotes sintering densification and reduces sintering temperature, thereby improving the material microstructure, reducing sintering stress, and improving the mechanical strength and magnetic properties of the material, thereby reducing the deformation of the inductor component.

[0120] By comparing Example 13 with Example 15, it can be found that Example 15 is significantly better than Example 13 in terms of saturation magnetic induction intensity, magnetic permeability and inductance change rate. Therefore, by combining the plasma treatment in the pretreatment of the scrapped NiCuZn material with the copper plating grain layer process, better microscopic performance and sintering performance are brought about, and the electromagnetic properties of the synthesized NiCuZn material are further improved, which is beneficial to reduce the deformation risk of the inductor component.

[0121] Comparing Comparative Examples 1-6 with Example 2, it can be seen that the additive of the present application adopts a specific V 2 O 5 、SiO 2 and CaO system, can effectively improve the uniformity of the microstructure, making the comprehensive performance of the prepared NiCuZn material more excellent.

[0122] Will Figure 1 and Figure 2 For comparison, Figure 1 is the differential thermal curve of the NiCuZn material obtained in Example 2, Figure 2 This is the differential thermal curve of the NiCuZn material prepared in Comparative Example 1. From the difference in energy change during the heating process of the NiCuZn material, it can be seen that the NiCuZn material prepared after adding the second main component, i.e., the scrapped NiCuZn material, has a more stable energy change during the firing process, especially in the high temperature zone (about 1000°C), which is more conducive to controlling its shrinkage deformation rate and stability during the product manufacturing process.

[0123] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, all equivalent changes made according to the principles of the present application should be included in the protection scope of the present application.

Claims

1. A NiCuZn material used in power inductor components, characterized in that: It comprises a first main component, a second main component and an additive; wherein the first main component comprises the following raw materials in weight percentage: 64-67wt% Fe2O3, 13-16wt% ZnO, 10-14wt% NiO, and the balance is CuO; Based on the weight of the first main component, the additive includes the following raw materials in weight percentage: 0.01-0.3wt% V2O5, 0.01-0.2wt% SiO2 and 0.01-0.2wt% CaO; The second main component is scrapped NiCuZn material, which is recycled NiCuZn material, wherein the main component includes the following raw materials in weight percentage: 67wt% Fe2O3, 13wt% ZnO, 12wt% NiO, and the balance is CuO; the addition amount of the second main component is 10-30wt% of the weight of the first main component; The second main component is ball-milled to control the particle size to 1.5-3 μm.

2. The NiCuZn material used in power inductor components according to claim 1, characterized in that: The additive includes the following raw materials in weight percentage: 0.08-0.22wt% V2O5, 0.06-0.15wt% SiO2 and 0.07-0.12wt% CaO.

3. The NiCuZn material used in power inductor components according to claim 1, characterized in that: The additives also include 0.1-0.26 wt % Bi2O3 and / or 0.05-0.3 wt % SrO.

4. A method for preparing the NiCuZn material used in power inductor components according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the raw materials of the first main component, ball milling once, and pre-calcining to obtain a pre-calcined material; S2, mixing the additive with the pre-burned material obtained in step S1, and performing secondary ball milling to obtain a mixed material; S3, mixing the second main component with the mixed material obtained in step S2 and stirring at high speed, adding a binder, continuing stirring, granulating, pressing and molding, and sintering to obtain the NiCuZn material used in the power inductor element.

5. The method for preparing NiCuZn material for use in power inductor components according to claim 4, characterized in that: In the step S1, the pre-burning temperature is 800-900° C. and the heat preservation time is 2-5 hours.

6. The method for preparing NiCuZn material for use in power inductor components according to claim 4, characterized in that: In the step S2, the particle size of the mixture after the secondary ball milling is 0.8-1 μm.

7. The method for preparing NiCuZn material for use in power inductor components according to claim 4, characterized in that: In step S3, the second main component is mixed and stirred with the mixed material after being pretreated, and the pretreatment includes the following steps: The second main component is ball-milled to control the particle size to 1.5-3 μm, placed in a 10-15wt% nitric acid solution, heated to 80-100°C, and kept warm for 20-30 minutes; filtered, washed, dried, plasma treated, and a copper grain layer is plated on the surface of the second main component by vacuum evaporation to obtain a pretreated second main component.

8. The method for preparing NiCuZn material for use in power inductor components according to claim 7, characterized in that: During the plasma treatment process, the treatment atmosphere includes a mixed gas of nitrogen and oxygen in a volume ratio of 1-3:5; the gas flow rate of the atmosphere is 260-300sccm; the treatment voltage is 300-370V; and the power is 3-4kW.

9. The method for preparing NiCuZn material for use in power inductor components according to claim 7, characterized in that: The thickness of the copper grain layer is 50-100 nm.

10. The method for preparing NiCuZn material for use in power inductor components according to claim 7, characterized in that: In the step S3, during the sintering process, the temperature is raised to 240-280°C at a heating rate of 3-5°C / min in the first stage, and the temperature is raised to 1050-1100°C at a heating rate of 1.2-2°C / min in the second stage, and then kept warm for 2.5-4h. In the third stage, the temperature is cooled at a cooling rate of 1.5-2°C / min, and the temperature is kept warm for 5min every time the temperature is reduced by 80-150°C, until the obtained NiCuZn material is cooled to room temperature.

Citation Information

Patent Citations

  • NiCuZn ferrite material and preparation method thereof

    CN103265275A

  • Cu, V, Bi and Co ion joint substitution method for preparing high-performance NiZn ferrite

    CN108863333A